The use of nanotechnology for treatment of multidrug resistant ovarian cancer cells - SAED, MELAD ELHADI (Trinity College Dublin. School of Medicine. Discipline of Histopathology, 2019)
The traditional ovarian cancer treatment includes a combination of surgery and chemotherapy. However, the prognosis for ovarian cancer following treatment is very poor in the majority of ovarian cancer patients, especially patients with stage III or IV disease on diagnosis. Many patients respond well initially to chemotherapy but go on to develop the recurrent chemoresistant disease. To improve the efficacy of chemotherapy, nanotechnology has been used in the targeting and treatment of ovarian cancer and it has been employed in cancer treatment to overcome some of the limitations seen with traditional therapy. In addition to their non-toxicity, low cost and commercial availability, nanodiamonds have many other advantages that can be utilized in drug delivery. They can be functionalized with different types of anticancer therapeutic and they can be suspended easily in water, which is important for biomedical applications. In this thesis, we have developed a novel nanocarrier using NDs coupled with 1st and 2nd line ovarian cancer chemotherapy (PTX, CARBO and DOX) and conjugated with ovarian cancer biomarkers (HE4 and CA125 antibodies) to deliver desired drugs to targeted cancer cells. The results of our study showed the nanocomplexes developed in our laboratory were successfully taken up by ovarian cancer cell lines and ovarian tumour explants. Cytotoxic effects were evaluated using different biological parameters such as cell viability, mitochondrial membrane changes, cell membrane permeability and cell cycle profiling. The changes of the biological parameters indicated the advantages of functionalised NDs for drug delivery. Moreover, the nanocomplexes induced a greater effect even at lower drug concentrations. Our developed nanocomplexes improved cytotoxicity in chemosensitive and chemoresistant ovarian cancer cell lines by activation of the apoptosis pathway through caspase-3 upregulation and non-stimulation of the drug transporter protein P-gp. Therefore, the nanocomplexes developed in our lab are a promising platform to effectively deliver anti-cancer chemotherapeutics to chemoresistant cancer cells that over express drug transporter proteins (P-gp). We have reported that LDH activity was elevated in ovarian tumour explants following exposure to drugs (PTX, CARBO and DOX) and the nanocomplex treatments, but not in untreated control ovarian tumour explants. We have also found that the nanocomplexes coupled with CARBO and DOX induced caspase-3 upregulation in the ovarian explants compared with the drugs alone. In summary, in vitro and ex vivo cytotoxic effects were seen after chemosensitive and chemoresistant ovarian cancer cell lines and ovarian tumour explants were treated with our developed nanocomplexes. The effect appears to be mediated by apoptosis and non-stimulation of P-gp. The use of nanodiamonds complexed to cytotoxic drugs and a specific target offers promise in improving the response of ovarian cancers to treatment and requires further investigation with in vivo studies.
APPROVED
Keywords: Nanotechnology, Nanodiamond, Ovarian Cancer, Multidrug Resistance Ovarian Cancer cell Lines.